(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The aim of the research is to evaluate the practice of banking departments for strategic foresight represented by its dimensions (environmental scanning, future vision, scenarios, reconfiguration) and its relationship to the organizational brilliance represented by dimensions (brilliance of leadership, brilliance of service and innovation, brilliance of knowledge, brilliance of employees), as the research was applied in A number of private Iraqi commercial banks represented by (Baghdad, Iraqi Investment, Iraqi Middle East Investment, Commercial Gulf, Ashur International Investment, Al Mansour Investment, Via Iraq Investment), and the research adopted the descriptive analytical approach using the questionnaire as a main tool in collecting its data from the sample. (165) officials at functional levels (senior management, middle management, executive management), as the statistical program (Spss v. 28) was used to calculate (weighted arithmetic mean, standard deviation, coefficient of variation, Pearson correlation coefficient, one-way analysis of variance) The research reached a number of conclusions, the most prominent of which were 1- There is a positive acceptance, at an average level, of the sample in the surveyed banks for the concept of strategic foresight. 2- There is a positive and strong correlation between strategic foresight and organizational brilliance. 3- The results of the research showed that there were no differences in the sample’s response to the research variables according to the personal variables